Effects of bromides of potassium and ammonium on some crops. (8th November 2019) - Shtangeeva, Irina; Niemelä, Matti; Perämäki, Paavo
Abstract: In this work, the response of wheat ( Triticum aestivum L.), rye ( Secale cereale L.), oat ( Avena sativa L.), and pea ( Pisum sativum L.) to bromides of potassium (KBr) and ammonium (NH4 Br) was studied. All plants were capable of accumulating high concentrations of bromine (Br). However, the Br accumulation depended on the Br compounds presented in the growth medium and plant species. The highest Br concentrations were observed in leaves and roots of the seedlings germinated in the medium spiked with KBr. Oat accumulated more Br than other plants and the lowest Br accumulation was observed in pea. The bioaccumulation of Br resulted in suppression of plant biomass and concentrations of several essential nutrients (K, Na, Ca, Mg, Zn and Cl). The most negative effects were caused by NH4 Br. Probably, this action was due to cumulative effects of Br - and NH4 + . Among other plant species, the most tolerant to bromides was oat and the most sensitive was wheat.